Preliminary studies on the use of chlorine water to control foot rot disease of pepper - Bong, Joseph Choon Fah; Ibrahim, Mohd Yusof (1985)
In Vitro studies at chlorine concentrations of 10, 50, 10O,300, 500 and 1000 ug/ml a.i. were conducted to test the effect of chlorine water on Phytophthora palmivora MF4 oringinally isolated from diseased roots of pepper (Piper nigrum L.) plant. Good mycelial qrowth inhibitions (44-98%) were obtained only during the first 3-4 days after treatment. The ED50 value was 34 ug/ml a.i. The potential use of chlorine as an alternative chemical to control the disease are discussed. Further trials are presently being conducted